PENGARUH BAHAN AJAR BERBASIS PBL TERINTEGRASI PENDEKATAN BERDIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Agusdianita, Neza; Yusnia (Jurnal PGSD, 2024)
This study aims to determine the effect of integrated pbl-based learning materials with a differentiation approach on the mathematics learning outcomes of fifth grade elementary school students. This type of research is quantitative research and the method used is a quasi-experimental method with the matching only pretest-posttest group design. The sample in this study was class VA of SDN 07 Bengkulu City as the experimental class and VB SDN 07 Bengkulu City as the control class. The instrument used was a written test sheet. Data collection used pretest and posttest which were analyzed with descriptive statistics and inferential analysis, namely the t-test. The results of this assessment showed that the posttest score had a significant difference between the experimental class and the control class. The conclusion of this study is that there is an effect of integrated pbl-based learning materials with a differentiation approach on the mathematics learning outcomes of fifth grade elementary school students.